The Impact of NPL and LLP on Profitability of Digital and Conventional Banks - Ronauli, Amelia Akiko; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Profitability is the most important aspect of conventional and digital banks in Indonesia. This has also been emphasized and expected by regulators so that banking profitability in Indonesia continues to increase. In addition, NPL and LLP as part of credit risk in conventional and digital banks in Indonesia experienced fluctuating trends and tended to increase in the previous few years, so this could affect the profitability of each bank. The study continued with the aim of re-identifying the effect of NPL and LLP on the profitability of digital banks and conventional banks in Indonesia using the panel data regression estimation method. Researchers used digital banks and conventional banks in Indonesia according to predetermined criteria. The results found that, NPL and LLP in conventional banks were found to have a significant negative impact on profitability. While in digital banks in Indonesia, NPL was found to have no impact on profitability and LLP had a significant negative impact. Thus, these findings are expected to help the banking industry and other regulators in evaluating and making policies related to increasing profitability in the Indonesian banking industry.